Future Challenges to The Federal System in Iraq - Aras Hasan Abdulqadir (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The federal system in Iraq faces many future challenges that this country is going through, because the constitutional reality contradicts its provisions due to the weakness or lack of political consensus between parties and the principle of national participation in accordance with constitutional and political foundations in the institutions of the state. In addition to that the Iraqi federalism is facing mysterious obstacles, due to the differences between political parties, which is the cause of division or dismantling. It is expected that the future relationship between the Kurdistan region and the federal government is likely to go through difficult stages, especially after the Kurdistan regional referendum on 25 September 2017 and the failure to adopt the federal system in Iraq properly in accordance with the provisions of the Constitution, which recognized the Kurdistan region as a result of its existence as a reality, and the new region faces many obstacles and challenges facing the federal system in Iraq in general.